Azucena - Davao, Ricky; Rivero, Dante; de Rossi, Allesandra; Mercado, Glydel; Siguion-Reyna, Carlos (Viva Films, 2001)
A story about the unlikely friendship between a man who butchers dogs for a living and an adolescent dog lover.